2014
DOI: 10.1021/op4003505
|View full text |Cite
|
Sign up to set email alerts
|

Combining Metabolic Pathway Design and Retrosynthetic Planning for the Design of a Novel Semisynthetic Manufacturing Scheme for Paclitaxel

Abstract: Using the example of paclitaxel, this paper expounds how retrosynthetic analysis can be combined with metabolic pathway design to devise novel semisynthetic schemes for manufacturing natural products. The analytical framework presented herein leverages the latest developments in chem-and bioinformatics, metabolic engineering, and retrosynthetic planning, and the proposed schemes commence with the microbially aided synthesis of an advanced intermediate that is then recruited for target-oriented synthesis (TOS).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…32,73 For instance, the taxane biosynthetic pathway that is expressed by trees of the Taxus genus synthesizes well over a hundred products, including paclitaxel, and strains of E. coli that were genetically engineered to express a few enzymes of the taxane pathway also produced a comparable diversity of molecules. 74 In this study, when the cytochrome P450 monooxygenase, taxadiene 5α-hydroxylase, was introduced into a strain of E. coli that had been previously engineered to overproduce taxadiene, it was observed that the cultures synthesized as many as 16 eicosanoid molecules (Figure 6).…”
Section: Applications In Diversity-oriented (Dos)mentioning
confidence: 79%
See 3 more Smart Citations
“…32,73 For instance, the taxane biosynthetic pathway that is expressed by trees of the Taxus genus synthesizes well over a hundred products, including paclitaxel, and strains of E. coli that were genetically engineered to express a few enzymes of the taxane pathway also produced a comparable diversity of molecules. 74 In this study, when the cytochrome P450 monooxygenase, taxadiene 5α-hydroxylase, was introduced into a strain of E. coli that had been previously engineered to overproduce taxadiene, it was observed that the cultures synthesized as many as 16 eicosanoid molecules (Figure 6).…”
Section: Applications In Diversity-oriented (Dos)mentioning
confidence: 79%
“…Once the combination of terpenoid biosynthetic enzymes that can or could produce the molecule of interest has been identified using the methodology that has been outlined in previous sections, they can be expressed without any modifications to their active site to generate a family of closely related structures that can then be subjected to hydroxyl hydrogen substitution reactions in vitro to yield an even larger library of highly “drug-like” molecules. Alternatively, if conventional TOS is desired (Figure ), the individual active sites can be re-engineered in order to enhance substrate specificity, product selectivity, and activity . For both, DOS and TOS schemes, the enzymes must be combined into a pathway, and enzyme expression must be suitably toggled in order to adjust their concentrations.…”
Section: Applications In Diversity-oriented (Dos) and Target-oriented...mentioning
confidence: 99%
See 2 more Smart Citations